Wine : a cultural history - Varriano, John L.; Mount Holyoke College. Art Museum; University of Rochester. Memorial Art Gallery (London : Reaktion Books, 2010)
From celebrations of Bacchus in ancient Rome to the Last Supper and casual dinner parties, wine has long been a key component of festivities, ceremonies, and celebrations. Made by almost every civilization throughout history, in every part of the world, wine has been used in religious ceremonies, inspired artists and writers, been employed as a healing medicine, and, most often, sipped as way to relax with a gathering of friends. Yet, like all other forms of alcohol, wine has also had its critics, who condemn it for the drunkenness and bad behavior that arise with its overconsumption. Wine can render you tongue-tied or philosophical; it can heal wounds or damage health; it can bring society together or rend it. In this fascinating cultural history of wine, John Varriano takes us on a tour of wine's lively story, revealing the polarizing effect wine has had on society and culture through the ages.
The origins of wine -- Wine in ancient Greece -- Roman wine -- Wine in the Middle Ages -- Renaissance wine -- The seventeenth and eighteenth centuries -- Modern wine -- Outside the Western tradition.
"This book was published to accompany the exhibition Wine and spirit: rituals, remedies, and revelry, organized by the Mount Holyoke College Art Museum [and held at] Mount Holyoke College Art Museum, South Hadley, Mass., USA, 2 Sept.-12 Dec. 2010 [and] Memorial Art Gallery of the University of Rochester, Rochester, N.Y., USA, 30 January-10 April 2011"--Title page verso.
Includes bibliographical references (pages 254-265) and index.
Joseph M. Carlin
Keywords: Wine -- Social aspects -- History; Wine and wine making -- History; Wine -- Social aspects -- Exhibitions; Wine in art; Wine in art -- Exhibitions; Wine in literature; Wine -- Physiological effect